Landfill Site Selection Using FAHP and GIS with Integration of MRF: A Case Study of Madhyabindu Municipality, Nawalparasi-East, Nepal - Subedi, Shanti Kala; Shrestha, Sujal; Mahato, Nabin; Shrestha, Nishan; Dahal, Sujan; Khatri, Sunil (Journal of Himalaya College of Engineering, 2025)
Solid waste disposal is a major challenge faced by communities across the world. Unplanned and unscientific way of dumping is leading to adverse effect in the environment and health factors. This study is carried out in Madhyabindu Municipality, located in Nawalparasi-East, Nepal where the one and only dumping site in Arunkhola river creating the urgency for a sustainable solution to reduce landfill dependency in a long term. An integrated approach combining Fuzzy Analytical Hierarchy Process (FAHP); Geographic Information System (GIS); and Material Recovery Facility (MRF) were employed. Seven criteria namely: Slope; Elevation; Land use; Land cover; Proximity to rivers; Forest; Roads; and Built-up areas were analyzed for ranking the criteria using FAHP. The study showed that an average waste generation rate at base year 2023 is 0.303kg/capita/day of which 61% is organic waste. By using weighted overlay suitability method in MRF only 0.9% of the total land area is found suitable and only 0.001% is highly suitable area for disposal. The way of using integrated approach to identify suitable site for waste disposal problems is highly useful to other sites also where similar condition exist.